1996
DOI: 10.1021/bi961593m
|View full text |Cite
|
Sign up to set email alerts
|

The Active State of the AT1 Angiotensin Receptor Is Generated by Angiotensin II Induction

Abstract: In the current model of receptor activation, the given hormone is not involved in the conversion of the inactive receptor (R) to the fully active state (R*). Rather, it preferentially selects the activated receptor conformation, thereby shifting the equilibrium toward R*. The hormone angiotensin II (Ang II) contains two residues, Tyr4 and Phe8, that are essential for agonism. We show that the conserved Asn111 in transmembrane helix III of the AT1 angiotensin receptor directly interacts with the Tyr4 side chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
204
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 148 publications
(217 citation statements)
references
References 28 publications
12
204
0
1
Order By: Relevance
“…1 is validated previously for compliance with experimentally determined interactions of AngII and losartan, as well as previous RCAM data (11,14). (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Functional interaction between receptor regions that are more than seven residues apart in the primary sequence and located at a distance greater than the hydrogen bonding distance (4 Å) in the tertiary structure is defined as long range interaction.…”
Section: Modeling Ecl2 In Relation To At1r Residues Asn 111 and Aspmentioning
confidence: 64%
“…1 is validated previously for compliance with experimentally determined interactions of AngII and losartan, as well as previous RCAM data (11,14). (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Functional interaction between receptor regions that are more than seven residues apart in the primary sequence and located at a distance greater than the hydrogen bonding distance (4 Å) in the tertiary structure is defined as long range interaction.…”
Section: Modeling Ecl2 In Relation To At1r Residues Asn 111 and Aspmentioning
confidence: 64%
“…First, in an AT 2 ͞AT 1 chimera receptor with the cytoloop 3 domain of AT 2 replaced by the corresponding region of AT 1 receptor, Ca 2ϩ movement was observed in the absence of Ang II stimulation (26). Second, Ang II binding profile has shown that in agreement with constitutively active AT 1 mutant N111G (27)(28)(29), AT 2 is insensitive to modifications of Ang II side chains at any position (22,30), suggesting that AT 2 receptor is already in a relaxed active state (R*). Third, Karnik's group has shown that AT 2 induces apoptosis in the absence of Ang II (25).…”
Section: Inactive Shp-1 Constitutively and Physically Associates Withmentioning
confidence: 94%
“…B a s e d o n a n u m b e r o f pharmacological, mutagenesis and computer-oriented modeling studies [63][64][65][66][67][68][69][70][71][72][73][74][75][76], the general agreement is that a positively-charged residue of Lys199 on transmembrane domain (TM)-5 of the AT1 receptor interacts with the -carboxyl group of Phe8 in Ang II. This interaction is crucial for high affinity binding of Ang II to the receptor.…”
Section: Functional Domains Of the At1 Receptormentioning
confidence: 99%